Description of the pupa of Culex (Culex) bidens Dyar (Diptera: Culicidae) - Rivera-García, Karina D.; Ibáñez-Bernal, Sergio (Zootaxa, 2018)
The pupa of Culex (Culex) bidens Dyar is described based on specimens from Mexico. The pupa is compared with the pupae of Culex (Culex) declarator Dyar & Knab and Culex (Culex) interfor Dyar, similar species which are easily confused with Culex bidens.